If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 2 + 6x = 8 Reorder the terms: 2 + -4x + 6x = 8 Combine like terms: -4x + 6x = 2x 2 + 2x = 8 Solving 2 + 2x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2x = 8 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 8 + -2 2x = 8 + -2 Combine like terms: 8 + -2 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| A=0.5h(7.3+14) | | 4(3x-1)=7-6x | | A+8+5a-12= | | 6x+2(4x-17)=92 | | N+3+5n=5+5n | | 4.9x^2+4x-2.25=0 | | 2x+18=16-4(x-7) | | -9v=7-10v | | 27-11=2(x-1) | | -9(-14f+-13)= | | 4x^2-11x-3= | | -2(5+6x)+14=-20 | | (x+18)(x-20)=0 | | 7(6+3x)=84 | | 2(-11-18q)= | | 6(5-8v)+12=-15 | | (2w-3)+w=78 | | 4(7v-4)-8=144 | | -2=5+3x | | y+2y+3y=150+(-12) | | y-9x=10 | | 4x+2x+x=42 | | 7-7n-2n=-8n+2 | | 7y*y= | | 2(5s+6)-4s=3(2s+3)-10 | | (a-b)(2a+ab)= | | 10(4h-16)= | | 8x+y=2x | | 6x^2-24x^2=0 | | 8t+2=t+5+t-3 | | 4n-2.8=8.8 | | 72=.75m |